Epidemiological Analysis of Mental Health Disorders in Patients at Psychiatric Hospitals in the Special Region of Yogyakarta, Indonesia - Rokhmayanti Rokhmayanti; Viandika Rulianawati; Fardhiasih Dwi Astuti; Siti Kunia Widi Hastuti; Rosyidah Rosyidah; Widea Rossi Desvita (Indonesian Journal of Medicine, 2023)
Background:  Mental disorder is a condition of decreasing all psychiatric conditions that result in deviant behavior. WHO estimates that one in eight people in the world lives with a mental disorder in the world. The COVID-19 pandemic that has occurred since 2019 has had an impact and has had a major impact on the mental health of people in the world and in Indonesia. The Special Region of Yogyakarta is the province with the highest cases of mental disorders in Indonesia based on the results of the 2013 and 2018 Basic Health Research (Riskesdas) surveys. The purpose of this study was to determine the epidemiological description of mental disorders per classification in inpatients at Mental Hospitals in the Special Region of Yogyakarta in 2019-2021.Subjects and Method:  This study used a quantitative descriptive method, sourced from secondary data from Mental Hospitals in the Special Region of Yogyakarta for the period 2019 - 2021. The population in this study was 4,413, with a total sample of 3,919. The inclusion criteria are data of inpatients with mental disorders recorded in the recapitulation of medical records of inpatients at the Mental Hospital for the period 2019 to 2021. Exclusion criteria are incomplete data. The sampling technique used is total sampling. The person variable consists of a classification of mental disorders, age, gender, education level, occupation, marital status, health insurance, and end of care. The instrument used in this research is a dummy table. Data from this study were analyzed descriptively by looking at the frequency and proportion of each variable studied.Results:  The results showed that the highest disease classification was F20-F29 (schizophrenia, schizotypal disorder, and delusional disorder) 76.72%. Most of them were aged 25-44 years (55.60%), male (61.55%), graduated from high school or equivalent (46.54%), did not work (66.90%), and were not married (57.29%). Most of them use national health insurance (62.95%), end of treatment with doctor's approval (97.86%), and length of stay ≤ 42 days (95.1%). Most of the patients came from Sleman Regency (37.25%) and from urban areas (71.37%).Conclusion:  Most patients with mental disorders are in productive age. People with mental disorders are an economic burden that must be borne by their families and the government. So there is a need for comprehensive prevention efforts to reduce the incidence of mental disorders in the community.Keywords:  mental disorders, epidemiological studies, schizophreniaCorrespondence: Siti Kurnia Widi Hastuti, Faculty of Public Health Universitas Ahmad Dahlan. Jl Prof Dr Soepomo Warungboto Umbulharjo, Special Region of Yogyakarta, Indonesia. Email: kurnia.widihastuti@ikm.uad.ac.id. Mobile: +62813-2843-3256.Indonesian Journal of Medicine (2023), 08(02): 204-218https://doi.org/10.26911/theijmed.2023.08.02.10